Relict hydrocarbon seeps in the Oligocene–Miocene Subis carbonate platform, Malaysia: Implications on hydrocarbon generation and migration pathways and potential sealing by shale gouging. (2nd June 2020) - Ramkumar, Muthuvairavasamy; Nagarajan, Ramasamy; J. Mathew, Manoj; Sautter, Benjamin; Siddiqui, Numair A.; Saw, Bing B.; Santosh, M.; Menier, David; Poppelreiter, Michael C.
Abstract : Occurrences of the highly productive, yet complex oil and gas‐ bearing Oligocene–Miocene buried carbonate platforms of the South China Sea and adjoining onshore equivalents necessitates understanding the form, timing and pathways of hydrocarbon migration plays. Here, we report the occurrence of structural‐stratigraphic controls on relict seepage and evaluate the hydrocarbon generation and migration pathway in the exposed Subis carbonate platform. Our results show that the seepages occur essentially along a post‐depositional fault plane located along the flank of a Miocene reef. The samples ( n : 3) contain 0.14–1.42% of total organic carbon (TOC). The Hydrogen Index (HI) varies between 72 and 147 Mg HC/g TOC and the Oxygen Index (OI) from 32 to 234 mg CO2 /g TOC. Similarly, the Production Index (PI) varies between 0.11 and 0.26. The source rock potentials are poor ( n = 2) and good ( n = 1). The studied samples show the T max uniformly as 433°C and PI values >0.1 and are therefore thermally immature. The occurrence of seepages sampled along the eastern flank of Subis buildup falls in the autochthonous field, indicating that the hydrocarbon was produced within the indigenous formation (Subis Limestone). This indicates absence of migration from deeper and older layers. However, occurrence of this seepage along a fault plane probably reactivated immediately after lithification of the Oligocene–Miocene carbonate bioherm and affected the matrix of the rocks, suggest that the hydrocarbon generated might have moved upward along this fault plane, assimilated into the host rock, especially in the finer matrix portions of the carbonates. The presence of CO2 at temperatures between 300–550°C is also suggestive of an organic matter origin or solution seams of the Subis Limestone and this inference obviates migration from deep‐seated faults and any connectivity and/or openness of the petroleum system between the subsurface and the atmosphere.